Brain imaging features in schizophrenia with co‐occurring auditory verbal hallucinations and depressive symptoms—Implication for novel therapeutic strategies to alleviate the reciprocal deterioration. Issue 2 (11th December 2020) - Zhuo, Chuanjun; Fang, Tao; Chen, Ce; Chen, Min; Sun, Yun; Ma, Xiaoyan; Li, Ranli; Tian, Hongjun; Ping, Jing
Abstract: Background: Auditory verbal hallucinations (AVHs) and depressive symptoms are highly prevalent in schizophrenia, and recent progress has been made in understanding the reciprocal deterioration of both symptoms through structural and functional brain imaging studies. To date, there is limited literature on this topic. In this review, we synthesized the recent literature on the neuroimaging features of schizophrenia patients with concurrent AVHs and depressive symptoms. Methods: A literature search was conducted with the major databases using the keywords, mainly including schizophrenia, AVHs, depression, neuropsychiatric disorders, brain imaging, and magnetic resonance imaging. Results: The existing studies have shown that AVHs and depressive symptoms reciprocally deteriorate in patients with schizophrenia, which has challenged the conventional treatment of the disease. Interestingly, repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) therapies have emerged as two efficacious brain stimulation treatments that can normalize the brain regions associated with the symptoms, as shown through functional and structural brain imaging studies. In light of these important findings, there is an urgent need to conduct in‐depth neuronal mechanistic studies to identify targets for stimulation therapy. Conclusions: These new findings may elucidate the pathological mechanisms underlying schizophrenia with concurrent AVHs and depressive symptoms. Furthermore, this review has important clinical implications for developing novel therapeutic strategies to alleviate the reciprocal deterioration AVHs and depressive symptoms of schizophrenia patients. Abstract : 1. Auditory verbal hallucinations (AVHs) and depressive symptoms are highly prevalent in schizophrenia. 2. The existing studies have shown that AVHs and depressive symptoms reciprocally deteriorate in patients with schizophrenia, which has posed changes in the conventional treatment of the disease. 3. There is an urgent need for in‐depth neuronal mechanistic studies to identify targets for the development effective therapies to alleviate the reciprocal deterioration.